Decision Support System for Smartphone Recommendations Based on Consumer Purchasing Power Using the AHP-PROMETHEE Method - Ary Santri Yuanda; Muhammad Dedi Irawan (Explorer, 2026)
The selection of smartphones that match consumer preferences and purchasing power is often challenging due to the large number of alternatives with varying specifications and prices. This research aims to develop a Decision Support System for smartphone recommendations using the Analytical Hierarchy Process (AHP) and Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) methods at R Ponsel Store. The AHP method was used to determine the priority weights of criteria based on the results of consumer preference questionnaires, while the PROMETHEE method was applied to rank smartphone alternatives. Data collection was conducted through observation, interviews, and literature studies. The criteria used include price, RAM, ROM, camera, processor, battery, and other supporting specifications. The results showed that the Consistency Ratio (CR) value was 0.035, indicating that the criteria comparison matrix was consistent. Based on the ranking results using the PROMETHEE method, the Redmi Note 14 8/256 achieved the highest net flow value of 0.042, making it the best alternative. The developed system is capable of assisting consumers in obtaining smartphone recommendations that better match their preferences and purchasing power